Financial constraints and corporate investment in China - Kun Mo; Michel Soudan (Bank of Canada, 2022)
Distortions in capital markets can create financial constraints that deter firms from pursuing optimal investment plans. This paper explores how much these constraints affect investment by ownership type in China, using a panel data model estimated with observations on listed firms for the period 2005-17. We find that privately owned enterprises (POEs) in China face greater financial constraints than state-owned enterprises (SOEs), as POE investment plans depend more on the availability of internally generated cash. Correspondingly, we find evidence that Chinese lenders appear less concerned about the credit risk of SOEs, and that an expansion in credit correlates with a disproportionally larger increase in investment for SOEs.
Keywords: E22; G1; G3; 330; Financial markets; Firm dynamics